Behavioral changes in the brown planthopper, Nilaparvata lugens, mediated by melatonin - Longqing Shi; Junian Zhang; Liangmiao Qiu; Zhaowei Jiang; Zhenxing Xie; Zhixiong Zhan (CABI Agriculture and Bioscience)
Abstract Background Melatonin has been proved to exist and play importance roles in rice plant, such as biosynthesis and resistance. However, little is known about the function of melatonin in its monophagous pest, the brown planthopper. Methods In this study, we examined the effects of melatonin on the copulatory and locomotor behaviors of brachypterous and macropterous adult planthoppers by exposing them to melatonin, luzindole (a melatonin receptor antagonist), or a combination of melatonin and luzindole. Results A total of 68.7% of copulation events occurred at night in the control, while 31.2% occurred at night in the melatonin treatment, which led to a decrease in offspring. Brachypterous males were involved in mating events in the melatonin treatment but not in the other two treatments or the control. The daily locomotor pattern in the melatonin treatment was markedly different from that in the luzindole and melatonin and luzindole treatments. The total locomotor activities of the macropterous and brachypterous males exposed with melatonin were suppressed compared to those in the control. Melatonin significantly decreased the daytime and nighttime locomotor activities of macropterous females. In comparison, the activity of brachypterous females decreased slightly in the daytime but was more than double that of the control females at night. Conclusions Our results reveal that melatonin plays a role in the behaviors of brown planthoppers.